Biomechanical assessment of screw safety between far cortical locking and locked plating constructs. Issue 6 (26th April 2021) - Deng, Yuping; Ouyang, Hanbin; Xie, Pusheng; Wang, Yanfang; Yang, Yang; Tan, Wenchang; Zhao, Dongliang; Zhong, Shizhen; Huang, Wenhua
Abstract: With the emerging concerns for more flexible and less stiff bridge constructs in the interest of stimulating bone healing, the technique of far cortical locking has been designed to reduce the stiffness of locked plating (LP) constructs while retaining construct strength. This study utilized simulation with diaphyseal bridge plating biomechanical models to investigate whether far cortical locking causes larger screw fracture risk than LP during rehabilitation. The fracture risk of the screws in the far cortical locking constructs increases in the non-osteoporotic and osteoporotic diaphysis compared with the screws in the LP constructs.